2004
DOI: 10.1126/science.1105660
|View full text |Cite
|
Sign up to set email alerts
|

United Time-Frequency Spectroscopy for Dynamics and Global Structure

Abstract: Ultrashort laser pulses have thus far been used in two distinct modes. In the time domain, the pulses have allowed probing and manipulation of dynamics on a subpicosecond time scale. More recently, phase stabilization has produced optical frequency combs with absolute frequency reference across a broad bandwidth. Here we combine these two applications in a spectroscopic study of rubidium atoms. A wide-bandwidth, phase-stabilized femtosecond laser is used to monitor the real-time dynamic evolution of population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
198
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(200 citation statements)
references
References 27 publications
2
198
0
Order By: Relevance
“…In addition to controlling nuclear dynamics, a femtosecond laser can be employed for high-resolution spectroscopy in ultracold systems by utilizing it as a frequency comb [21]. These two limits have recently been combined in a spectroscopic study with coherent pulse accumulation [22]. The appeal of such an approach lies in the fact that with a femtosecond frequency comb it is possible to continuously switch between the two limits, selecting the desired time and frequency resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to controlling nuclear dynamics, a femtosecond laser can be employed for high-resolution spectroscopy in ultracold systems by utilizing it as a frequency comb [21]. These two limits have recently been combined in a spectroscopic study with coherent pulse accumulation [22]. The appeal of such an approach lies in the fact that with a femtosecond frequency comb it is possible to continuously switch between the two limits, selecting the desired time and frequency resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, larger differences between pulse propagations with symmetric and asymmetric detunings are obtained for energies that do not satisfy the one-photon resonance condition [9], since the twophoton Raman resonance is always fulfilled for symmetric detunings. There is one exception, when a similar behavior of the pulse propagation leading to EIT is obtained for asymmetric detunings that do not correspond to one-photon resonance, δ p = −δ c = (2 m p + 1) ω r /2, because the twophoton Raman detuning is again a multiple of the repetition angular frequency and therefore the twophoton resonance condition is satisfied, as shows, in Fig.…”
Section: Propagation Of Probe and Coupling Laser Pulsementioning
confidence: 99%
“…By using a comb laser, which means an ultrafast laser pulse train with a high repetition rate, one can carry out the ultrahigh resolution spectroscopy. Recently it has been shown that the accumulation ef-fects of coherence by a laser pulse train play an important role for coherent control of atomic or molecular systems [9,10]. The use of a chirped laser pulse train is another way for coherent control of population transfer [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, individual comb components can be tuned to scan over the frequency gap. [16][17][18][19][20][21] Other methods include spatially separating the comb lines using gratings, 21 Fourier transform spectroscopy of a single OFC 22 and dual-mode spectroscopy using two OFCs. 23,24 Nevertheless, few efforts have been made to decrease the comb spacing to improve the spectral resolution.…”
Section: Introductionmentioning
confidence: 99%